Interactions and Solubilization of Poorly Soluble Drugs in Aerosol-OT Micelles - GÖKTÜRK, SİNEM (WILEY, 2018)
Absorption spectroscopy, conductivity, and surface tension measurements were carried out at 298K to study the solubilization of poorly soluble drugs sulfamethoxazole (SMX) and trimethoprim (TMP) in Aerosol-OT (AOT) micellar media. The binding constants of SMX and TMP to AOT micelles were determined by applying the Benesi-Hildebrand equation. A comparison of the binding constants indicates that the binding tendency of TMP with AOT micelles is higher than that of SMX. To better analyze the incorporation of drugs into anionic AOT micellar media, surface tension measurements were performed in the presence of SMX and TMP in aqueous media. The influence of TMP and SMX on the surface properties of AOT was determined using the Gibbs Adsorption Isotherm. Changes in the surface properties of AOT determined by surface tension measurements in the presence of drugs are in good agreement with the binding constants determined spectrophotometrically. Calculated surface parameters indicate higher incorporation of TMP with AOT than that of SMX. Comparison of the aqueous solubility of TMP and SMX with micellar media indicated solubility enhancements for both poorly soluble drugs. A special attempt was made to highlight simultaneous interactions of TMP and SMX with AOT using both surface tension and conductometric measurements that can be used to determine counterion-binding parameters.
Keywords: Sulfamethoxazole; Trimethoprim; Micellar solubilization; Binding constant; Surface tension; Spectrophotometry; SODIUM DODECYL-SULFATE; AMPHIPHILIC DRUG; AMITRIPTYLINE HYDROCHLORIDE; ZWITTERIONIC SURFACTANTS; MICELLIZATION BEHAVIOR; DIFFERENT TEMPERATURES; ELECTRONIC ABSORPTION; MOLECULAR INTERACTION; AQUEOUS-MEDIUM; FLUORESCENCE